Recent Progress of Stem Cell Therapy in Cancer Treatment: Molecular Mechanisms and Potential Applications - Dinh-Toi Chu; Tiep Tien Nguyen; Nguyen Le Bao Tien; Dang-Khoa Tran; Jee-Heon Jeong; Pham Gia Anh; Vo Van Thanh; Dang Tien Truong; Thien Chu Dinh (Cells, 2020)
The insufficient and unspecific target of traditional therapeutic approaches in cancer treatment often leads to therapy resistance and cancer recurrence. Over the past decades, accumulating discoveries about stem cell biology have provided new potential approaches to cure cancer patients. Stem cells possess unique biological actions, including self-renewal, directional migration, differentiation, and modulatory effects on other cells, which can be utilized as regenerative medicine, therapeutic carriers, drug targeting, and generation of immune cells. In this review, we emphasize the mechanisms underlying the use of various types of stem cells in cancer treatment. In addition, we summarize recent progress in the clinical applications of stem cells, as well as common risks of this therapy. We finally give general directions for future studies, aiming to improve overall outcomes in the fight against cancer.